Pendekatan Lean Six Sigma Dalam Penentuan Prioritas Perbaikan Layanan Bank Berdasarkan Persepsi, Harapan Dan Kepentingan Nasabah - Hesti Budiwati (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This research have a purpose to determine ofimprovement priority of bankingservicesbase on perception, expectation and interest level of the customer using lean sigsigma approach. The result of this research are expected to give the contribute for thebank manager. This research will determine to recovery priority of service quality of thebank consisted of (1) effectiveness and assurance, (2)access, (3) price, (4) tangible, (5)service portofolio and (6) reliability.This research using lean sig sigma approach, to doingthe calculation unwighted gap and weighted gap above the response of respondent baseon perception, exspectation and interest level of the customer above the response of theresponden base on perception, exspectation and interest level of the customer aboveservive quality of the bank. The population of this research is all active customera at PT.BPR Arta Centra Asia Lumajang,and sample of this research is taken as 120 customer asrespondent. The result of this research showing at 3 (three) main priority of the recoveryquality service of the bank that is dimension to reliability for the item the dont have amistake in providing service, the dimension of the effectiveness is no delay because thebirocation and procedure and service quickly.The next future this research are exspectedto give the contribution to development of the study management science, especially for marketing management service, so it can be a reference for the similiarity of research andadvance research.